2012
DOI: 10.1242/dmm.009274
|View full text |Cite
|
Sign up to set email alerts
|

Facial dysmorphism induced by bone morphogenetic protein receptor type 1A-mediated signaling reduction in neural crest-derived cells

Abstract: SUMMARYBone morphogenetic protein (BMP) receptor type 1A (BMPR1A) mutations are associated with facial dysmorphism, which is one of the main clinical signs in both juvenile polyposis and chromosome 10q23 deletion syndromes. Craniofacial development requires reciprocal epithelial/neural crest (NC)-derived mesenchymal interactions mediated by signaling factors, such as BMP, in both cell populations. To address the role of mesenchymal BMP signaling in craniofacial development, we generated a conditional knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Some of these genes, e.g., BMPR1A (601299) , LDB3 (605906), GRID1 (610659), and NRG3 (605533), have been hypothesized as putative candidate genes associated with the phenotype, especially regarding the neuropsychological development and cardiac defects [Balciuniene et al, 2007;van Bon et al, 2011;Breckpot et al, 2012]. Saito et al [2012] evaluated heart morphology of the mutant mouse knockout BMPR1A protein in neuralcrest-derived cells and showed that some of them exhibited facial fusion defects such as a cleft face and cleft palate, or facial dysmorphic features besides heart defects. Thus, the craniofacial dysmorphisms and CHD observed in our patient may be partly caused by the deletion in the BMPR1A gene.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these genes, e.g., BMPR1A (601299) , LDB3 (605906), GRID1 (610659), and NRG3 (605533), have been hypothesized as putative candidate genes associated with the phenotype, especially regarding the neuropsychological development and cardiac defects [Balciuniene et al, 2007;van Bon et al, 2011;Breckpot et al, 2012]. Saito et al [2012] evaluated heart morphology of the mutant mouse knockout BMPR1A protein in neuralcrest-derived cells and showed that some of them exhibited facial fusion defects such as a cleft face and cleft palate, or facial dysmorphic features besides heart defects. Thus, the craniofacial dysmorphisms and CHD observed in our patient may be partly caused by the deletion in the BMPR1A gene.…”
Section: Discussionmentioning
confidence: 99%
“…Other rare features are micrognathia, low-set or posteriory-rotated ears, and epicanthal folds; the patient presented here is the first one exhibiting a mediane cleft palate. In a recent publication, Saito et al [2012] presented a conditional knockout mouse model, generated by expressing a dominant negative BMPR1A protein (dnBMPR1A) in neuralcrest-derived cells (dnBMPR1A lacks the intracellular kinase domain and, thus, inhibits the BMPR1A-mediated signaling pathway). The mutant mice exhibited either facial fusion defects such as a cleft face and cleft palate, or facial dysmorphology corresponding to hypertelorism and flat nasal bridge in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing literature for cases with distal chromosome 10q deletions and using computed gene prioritization, the authors showed that BMPR1A is the best candidate gene for CHD in patients with 10q22q23 deletions. Saito et al [2012] also evaluated heart morphology of the mutant animals and showed that some of those with a facial cleft exhibited a ventricular septum defect as well. Thus, deletions of BMPR1A may contribute to various phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis due to augmented BMP signaling is seen in several craniofacial structures [35, 120, 121]. Smad-dependent BMP signaling prevents degradation of p53, and increased levels of p53 augment downstream targets, such as Bax and caspase-3 to promote apoptosis.…”
Section: Common Mechanism and Outlookmentioning
confidence: 99%